Fungal Bioremediation of Creosote-contaminated Soil - Byss, Marius (Jihočeská univerzita, 2009)
The influence of two ligninolytic fungi (Pleurotus ostreatus and Irpex lacteus) on bioremediation of creosote-contaminated soil was studied. The thesis describes the polycyclic aromatic hydrocarbon concentration decrease during the laboratory-scale experiments and reveals the changes in the present soil microbial community under the influence of either fungus. The thesis compares different impact on PAH concentrations and soil microbial community depending on the fungus applied.
Fungal Bioremediation of Creosote-contaminated Soil